2021
DOI: 10.1037/men0000367
|View full text |Cite
|
Sign up to set email alerts
|

The politics of men’s and women’s traditional masculinity ideology in the United States.

Abstract: Little is known about how men's and women's traditional masculinity ideology (TMI; patriarchal beliefs about the norms for men's thoughts, feelings, and behaviors) relates to political ideology in the United States. The present study used bifactor modeling to examine the relative contributions of seven norms of TMI, as measured by the Male Role Norms Inventory-Short Form (MRNI-SF), as predictors of conservative political ideology (CPI). Structural equation modeling in a sample of 1,136 U.S. participants (78% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
(117 reference statements)
1
7
1
Order By: Relevance
“…Unexpectedly, when we included political ideology (rather than party), the effects of HM on evaluations of political leaders’ responses to COVID-19 were minimized (see Supplemental materials). In addition, recent research has shown a strong association between traditional masculinity and conservativism (McDermott et al, 2021). Although beyond the scope of the present data and analyses, it is possible that evaluations of political leaders’ responses to COVID-19 were confounded with participants’ general political beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, when we included political ideology (rather than party), the effects of HM on evaluations of political leaders’ responses to COVID-19 were minimized (see Supplemental materials). In addition, recent research has shown a strong association between traditional masculinity and conservativism (McDermott et al, 2021). Although beyond the scope of the present data and analyses, it is possible that evaluations of political leaders’ responses to COVID-19 were confounded with participants’ general political beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Various categories of adherence to gender norms (e.g., belief endorsement, behavioral conformity) are individual difference variables that are also linked with many other demographic variables and aspects of identity. For example, the endorsement of traditional masculinity ideology is inversely related to socio-economic status (SES; Wimer & Levant, 2013) and positively correlated with political ideology (McDermott et al, 2021), among other correlates with other demographic variables (see Levant & Richmond, 2016, for a review). Therefore, it is reasonable to assume that boys from more politically conservative homes and those lower in SES would be more strongly socialized to conform to masculine norms.…”
Section: Feminist and Gender Role Socialization Theoriesmentioning
confidence: 99%
“…Republicans (vs. Democrats) and men (vs. women) were also more likely to believe that America is growing ''soft and feminine'' (i.e., gendered nationalism), and this belief led to a greater likelihood of voting for Trump in 2016 (Deckman & Cassese, 2019). In addition, and consistent with the notion that masculinity functions as a cultural ideology, men and women who define themselves using more masculine (vs. feminine) personality traits more strongly identify with the Republican party (McDermott, 2016) and endorsement of masculine ideology is associated with conservatism for both men and women (McDermott et al, 2021).…”
Section: Masculinity and Politicsmentioning
confidence: 75%